Effects of different types of biochar on methane and ammonia mitigation during layer manure composting. (March 2017) - Chen, Wei; Liao, Xindi; Wu, Yinbao; Liang, Juan Boo; Mi, Jiandui; Huang, Jinjie; Zhang, Heng; Wu, Yu; Qiao, Zhifen; Li, Xi; Wang, Yan
Highlights: Biochar reduces NH3 and CH4 emissions during layer-hen manure composting. Cornstalk biochar is most effective in reducing pH and enhance the nitrification during composting. NH3 loss was correlated with the surface area, pore volumes, total acidic functional groups and CEC of biochar. Abstract: Biochar, because of its unique physiochemical properties and sorption capacity, may be an ideal amendment in reducing gaseous emissions during composting process but there has been little information on the potential effects of different types of biochar on undesired gaseous emissions. The objective of this study was to examine the ability and mechanism of different types of biochar, as co-substrate, in mitigating gaseous emission from composting of layer hen manure. The study was conducted in small-scale laboratory composters with the addition of 10% of one of the following biochars: cornstalk biochar, bamboo biochar, woody biochar, layer manure biochar and coir biochar. The results showed that the cumulative NH3 production was significantly reduced by 24.8 ± 2.9, 9.2 ± 1.3, 20.1 ± 2.6, 14.2 ± 1.6, 11.8 ± 1.7% (corrected for initial total N) in the cornstalk biochar, bamboo biochar, woody biochar, layer manure biochar and coir biochar treatments, respectively, compared to the control. Total CH4 emissions was significantly reduced by 26.1 ± 2.3, 15.5 ± 2.1, 22.4 ± 3.1, 17.1 ± 2.1% (corrected for the initial total carbon) for cornstalk biochar, bamboo biochar, woody biochar and coir biochar treatments than the control. Moreover, addition of cornstalk biochar increased the temperature and NO3 − -N concentration and decreased the pH, NH4 + -N and organic matter content throughout the composting process. The results suggested that total volatilization of NH3 and CH4 in cornstalk biochar treatment was lower than the other treatments; which could be due to (i) decrease of pH and higher nitrification, (ii) high sorption capacity for gases and their precursors, such as ammonium nitrogen from composting mixtures, because of the higher surface area, pore volumes, total acidic functional groups and CEC of cornstalk biochar.